Pendekatan Top-Down dan Bottom-Up antara Pemerintah Pusat dan Pemerintah Daerah Masa Pandemi Covid-19 - Illiyyina, Izzah; Rosa, Nabila Septia (Public Sphere Review, 2025)
During the pandemic of Covid-19, Indonesia experienced the dynamic relationship between the central government and local government. The central government used the top-down model, implementing Covid-19 management policies in an agency model, which limited local government authority to the central government's representatives. This research uses a qualitative method of literature study, using secondary data sources obtained from books, supporting articles, scientific papers, previous studies and other literature. This resulted in pro-contracted decision-making, with some heads of districts implementing local initiatives without prior instructions. Top-down emphasize a capacity of central policy makers to set clear objectives and closely oversee the implementation process, while bottom-uppers emphasize the autonomy of the bottom and the discretion exercised by local bureaucrats. The national government and the province of DKI Jakarta have not coordinated their policy initiatives, with the central government suggesting relaxation of the social distancing policy. Weak collaboration and miscommunication between central and local governments can lead to failure in policy implementation.